2015
DOI: 10.1371/journal.pcbi.1004631
|View full text |Cite
|
Sign up to set email alerts
|

Simulations Meet Experiment to Reveal New Insights into DNA Intrinsic Mechanics

Abstract: The accurate prediction of the structure and dynamics of DNA remains a major challenge in computational biology due to the dearth of precise experimental information on DNA free in solution and limitations in the DNA force-fields underpinning the simulations. A new generation of force-fields has been developed to better represent the sequence-dependent B-DNA intrinsic mechanics, in particular with respect to the BI ↔ BII backbone equilibrium, which is essential to understand the B-DNA properties. Here, the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 80 publications
4
23
0
Order By: Relevance
“…These were chosen because GpY and ApC steps show the highest BII propensities among RpY steps from MD simulations (75% and 60% BII respectively, see Figure 1B). The reader should be aware that when comparing NMR, MD simulations, and X-ray structures, differences exist between the specific BII percentages assigned to some base pairs steps 12,21 . The sources of uncertainties from crystal structures have being discussed several times and are clearly related to low resolution (frequently insufficient to define backbone's states), lack of dynamics, and lattice restraints 13,25,26 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These were chosen because GpY and ApC steps show the highest BII propensities among RpY steps from MD simulations (75% and 60% BII respectively, see Figure 1B). The reader should be aware that when comparing NMR, MD simulations, and X-ray structures, differences exist between the specific BII percentages assigned to some base pairs steps 12,21 . The sources of uncertainties from crystal structures have being discussed several times and are clearly related to low resolution (frequently insufficient to define backbone's states), lack of dynamics, and lattice restraints 13,25,26 .…”
Section: Resultsmentioning
confidence: 99%
“…Equivalent results were obtained for YpR and YpY steps (Table S2 and Figure S4). It should be noted that in spite of the extended set of structures used in this work, BII propensities from crystal structures still seems underestimated when compared with NMR and MD results (Table S2) [4][5][6]12,20,21 . The reasons for the apparent discrepancies between the methods, which are beyond the scope of the present work, are complex, of diverse sources, and have been partially addressed recently 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, RY steps appeared to be rigid and exhibited the sparsest dynamics. Structural and dynamic studies by our group and others have revealed that base pair step dynamics are correlated with conformational transitions in the sugar-phosphate backbone and variations in minor and major groove widths [110,[112][113][114]116]. Spontaneous backbone transitions from BI/BI step to the mixed BI/BII or BII/BII state were commonly observed in all these studies, alongside a decrease in roll and increase in slide and twist (in BI, ε/ζ torsions are in t/g-; in BII, ε/ζ torsions are in g−/t conformation).…”
Section: Local Noncanonical Dynamics Of the Canonical B-dnamentioning
confidence: 96%
“…Global deformations have been studied using single-molecule techniques, cyclization experiments [104], atomic force microscopy [105], molecular force sensors [106] and FRET [107]. With significant advances in atomistic force fields and computational power, microsecond-long state-ofthe-art MD simulations are now possible and have contributed immensely to our understanding of motions in the B-DNA helix [103,[108][109][110][111][112][113][114]. Key findings obtained from these MD simulation studies will be reviewed here.…”
Section: Structural Polymorphism In Double-stranded Dnamentioning
confidence: 99%